The Influence of Original Local Government Revenue and Capital Expenditures on Economic Growth and Community Welfare - Nurharibnu Wibisono; Suprayitno Eko; Asnawi Nur (Jurnal Ekonomi Pembangunan, 2024)
This study examined how capital expenditures and Original Local Government Revenue (PAD) affected community well-being in Bakorwil 1 Madiun, East Java districts and cities between 2015 and 2022. The analysis was mediated by economic growth. This study's saturation sample comprised ten Bakorwil 1 Madiun districts/cities. The Directorate General of Fiscal Balance (DJPK) website of the Ministry of Finance of the Republic of Indonesia provided secondary statistics on the realization of capital expenditures (CE) and PAD. On the Central Statistics Agency (BPS) website, secondary statistics on community welfare (HDI) and economic growth (GRDP) are available for download in different district/city editions for Bakorwil 1 Madiun. Path analysis is used in data analysis. The study's findings indicate that PAD has a significant positive relationship with HDI and GRDP. CE has a significant negative effect on HDI and GRDP partially. GRDP has a considerable positive impact on HDI. GRDP mediates a significant positive effect of PAD on HDI. GRDP does not mediate the impact of CE on HDI.